Comparative effect of different cooking methods on the physicochemical and sensory characteristics of high pressure processed marinated pork chops. (June 2019) - O'Neill, Ciara M.; Cruz-Romero, Malco C.; Duffy, Geraldine; Kerry, Joe P.
Abstract: The objective of this study was to assess the effect of griddle and steam cooking on the physicochemical and sensory characteristics of high pressure processed (HPP) piri-piri marinated pork chops (MPC). Raw MPC that were HPP at 400 MPa had higher ( P  < 0.05) marinade absorption compared to untreated samples. After cooking, griddled MPC were significantly ( P  < 0.05) darker, less red, less yellow, tougher and had higher cook loss compared to steam cooked samples. The appearance of the griddled MPC was preferred while the texture, tenderness, juiciness and overall sensory acceptability (OSA) were preferred in steam cooked MPC. The increased marinade absorption in MPC that were HPP modified the fatty acid composition resulting in increased ( P  < 0.05) levels of oleic acid (C18:1c). Steam cooked MPC had a lower ( P  < 0.05) n-6: n-3 PUFA ratio and were preferred by the sensory panel compared to griddled MPC. Overall, from the cooking methods assessed steam cooking was the best cooking method for untreated and MPC that were HPP. Industrial relevance: Processed meat manufacturers are constantly looking for new ways to increase yield, safety and shelf life of meat products. While high pressure processing (HPP) of raw meat has been shown to increase the safety and shelf life of these products; however, negative effects on the physicochemical characteristics of raw meat products have been reported. For example, HPP of raw meat products causes a whitening effect which may negatively affect consumers' acceptance of these products. In this study, we used a novel approach (a combination of HPP, marinade and a mix of organic acids Inbac™) which showed great potential not only for enhancing the yield of marinated pork chops but also enhancement of the sensory properties, safety and shelf life and particularly the piri-piri marinade masked the discoloration of raw pork meat caused by HPP. This study also provides consumers, retailers and caterers with information on how to best prepare HPP meat products and showed that steam cooked HPP marinated pork chops had the best physicochemical and sensory characteristics compared to griddled marinated pork chops. Highlights: High pressure processing (HPP) increased marinade flavour absorption in pork chops Enhanced marinade absorption modified the fatty acid composition of marinated pork chops (MPC) Cooking methods (Steam or Griddle) affected the physicochemical & sensory characteristics of MPC Steam cooked MPC that were HPP had better physicochemical characteristics compared to griddled MPC Steam cooked MPC that were HPP had the best sensory characteristics compared to griddled MPC